Festival and special event management - McDonnell, Ian. (John Wiley and Sons, 1999)
What are specialevents? The impacts of special events. Conceptualising the event. The planning function. Leadership and human resources. The marketing of events. Sponsorship of events. Control and budgets. Legal and risk management.. Logistics. Staging events. Evaluation and reporting.